Amygdala responses to unpleasant pictures are influenced by task demands and positive affect trait - Sanchez, Tiago A.; Mocaiber, Izabela; Erthal, Fatima S.; Joffily, Mateus; Volchan, Eliane; Pereira, Mirtes G.; de Araujo, Draulio B.; Oliveira, Leticia (Frontiers in Human Neuroscience, 2015)
The role of attention in emotional processing is still the subject of debate. Recent studies have found that high positive affect in approach motivation narrows attention. Furthermore, the positive affect trait has been suggested as an important component for determining human variability in threat reactivity. We employed fMRI to investigate whether different states of attention control would modulate amygdala responses to highly unpleasant pictures relative to neutral and whether this modulation would be influenced by the positive affect trait. Participants (n=22, 12 male) were scanned while viewing neutral (people) or unpleasant pictures (mutilated bodies) flanked by two peripheral bars. They were instructed to (a) judge the picture content as unpleasant or neutral or (b) to judge the difference in orientation between the bars in an easy condition (0º or 90º orientation difference) or (c) in a hard condition (0º or 6º orientation difference). Whole brain analysis revealed a task main effect of brain areas related to the experimental manipulation of attentional control, including the amygdala, dorsolateral prefrontal cortex and posterior parietal cortex. ROI analysis showed an inverse correlation (r = -0.51, p < 0.01) between left amygdala activation and positive affect level when participants viewed unpleasant stimuli and judged bar orientation in the easy condition. This result suggests that subjects with high positive affect exhibit lower amygdala reactivity to distracting unpleasant pictures. In conclusion, the current study suggests that positive affect modulates attention effect on unpleasant pictures, therefore attenuating emotional responses.